Pengembangan usaha minuman berbasis pangan fungsional “ON SPOT” di Kota Pekanbaru - Angga Pramana; Jum’atri Yusri; Evy Rossi; Rusli Rustam; Yelmira Zalfiatri; Rahmayuni Rahmayuni (Unri Conference Series: Community Engagement, 2021)
ON SPOT is a street vendor business engaged in contemporary beverages with the main ingredients of functional food yogurt and kefir. Not long ago, ON SPOT experienced problems in the form of losing its market due to restrictions on community activities during the pandemic, so it had to change the target market from students to housewives to stay afloat. The strategy is to process yogurt and kefir into mambo ice sticks that are more easily accepted by housewives. However, it is necessary to make good business development efforts so that products are more accepted by consumers such as products that have been produced with Good Manufacturing Practice (GMP) standards and have business legality to ensure product quality. The methods carried out in community counseling are in the form of training and mentoring approaches to ON SPOT, so that ON SPOT can develop business better and have business legality. Entrepreneurial devotion activities carried out, produce ON SPOT products produced with GMP standards so as to ensure products are safe to consume and have legality in the form of business licenses.